A cost-effectiveness analysis of delayed breast reconstruction with pedicled flaps from the back. Issue 7 (July 2022) - Makki, Ahmad; Thomsen, Jørn B.; Gunnarsson, Gudjon L.; Hölmich, Professor Lisbet R.; Sørensen, Professor Jens A.; Rindom, Mikkel B.
Summary: Background: Variability in breast reconstruction methods provides an opportunity to investigate whether a method is superior to another with regard to cost, quality, or both. We performed a cost-effectiveness analysis (CEA) study based on tertiary endpoint data from a randomized clinical trial to compare the cost-effectiveness of delayed breast reconstruction by either a latissimus dorsi flap (LD) or a thoracodorsal artery perforator flap (TAP). Material & methods: A total of 50 women were included for unilateral delayed breast reconstruction and were randomized to reconstruction by either the LD flap ( n  = 18) or the TAP flap ( n  = 22). The CEA was based on differences in shoulder function after the reconstruction. Direct and indirect costs relating to the two procedures were assessed by the Danish Diagnosis-Related Groups tariffs. Results: Our analysis showed a significant positive effect of introducing the TAP flap on the total shoulder score with an additional cost of $2779. The incremental cost-effectiveness ratio was $4481 and based on a willingness to pay (WTP) $500, we found an estimated net benefit of $519, which was statistically significant ( p  = 0.0375). The cost-effectiveness acceptability curve indicated that there is a 96.3% probability for the TAP flap being cost-effective to the LD flap at a WTP threshold of $500. Conclusion: From a societal perspective, our cost-effective analysis demonstrated that the TAP flap is the more cost-effective method of breast reconstruction compared to the LD flap with respect to patient-reported shoulder-related disability.